Evaluasi Hasil Layanan Konseling Individual di Sekolah Menengah Atas Yogyakarta - Widyatmoko, Wahyu; Purwanta, Edi (Jurnal Kajian Bimbingan dan Konseling, 2019)
This research aimed to evaluate the implementation of individual counseling results at Muhammadiyah 3 Yogyakarta Senior High School. Evaluation model used was gap (discrepancy evaluation model). In addition, population in this research was students who had attended individual counseling. Furthermore, research samples were 104 students, obtained by using proportionate stratified random sampling technique. Data collection used was individual counseling scale. The data was analyzed using descriptive statistics. Findings indicated that the majority of individual counseling results was in good criteria.